Current management of severe acquired aplastic anemia - Phillip Scheinberg (Einstein (São Paulo), 2011)
Overall survival in severe aplastic anemia has markedly improved in the past four decades due to advances in stem cell transplantation, immunosuppressive therapies and supportive care. Horse anti-thymocyte globulin plus cyclosporine is the standard immunosuppressive regimen in severe aplastic anemia, and often employed as initial therapy as most are not candidates for a matched related stem cell transplantation. With this regimen, hematologic response can be achieved in 60 to 70% of cases, but relapse is observed in 30 to 40% of responders and clonal evolution in 10 to 15% of patients. Efforts to improve outcomes beyond horse anti-thymocyte globulin plus cyclosporine have been disappointing, with no significant improvement in the critical parameter of hematologic response, which strongly correlates with long-term survival in severe aplastic anemia. Furthermore, rates of relapse and clonal evolution have also not improved with the development of three drug regimens or with more lymphocytotoxic therapies. Therefore, horse anti-thymocyte globulin plus cyclosporine remains the standard immunosuppression of choice as first therapy in severe aplastic anemia. Interestingly, survival has markedly improved over the years in large part due to better anti-infective therapy and more successful salvage therapies with immunosuppression and stem cell transplantation. In this review general aspects of diagnosis and management are discussed.